2015
DOI: 10.1080/03670244.2015.1080166
|View full text |Cite
|
Sign up to set email alerts
|

Field testing a questionnaire assessing parental psychosocial factors related to consumption of calcium-rich foods by Hispanic, Asian, and Non-Hispanic white young adolescent children

Abstract: Intervention strategies to increase calcium intake of parents and young adolescent children could be improved by identifying psychosocial factors influencing intake. The objective was to develop a tool to assess factors related to calcium intake among parents and Hispanic, Asian, and non-Hispanic white young adolescent children (10-13 years) meeting acceptable standards for psychometric properties. A parent questionnaire was constructed from interviews conducted to identify factors. Parents (n = 166) in the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Participants and settings from different socioeconomic backgrounds were included in most of the included studies. In four of the studies where information was provided by parents, the sample was predominantly made up of mothers [ 33 , 34 , 37 , 48 ]. In the studies where children or adolescents provided information, both male and female participants were included.…”
Section: Resultsmentioning
confidence: 99%
“…Participants and settings from different socioeconomic backgrounds were included in most of the included studies. In four of the studies where information was provided by parents, the sample was predominantly made up of mothers [ 33 , 34 , 37 , 48 ]. In the studies where children or adolescents provided information, both male and female participants were included.…”
Section: Resultsmentioning
confidence: 99%
“…These findings mirror the results yielded from another study among store owners and managers, in a predominantly Latino neighborhood, that revealed that the social environment (customer services and interpersonal dynamics) of small stores largely influence customers’ patronage. 14 …”
Section: Discussionmentioning
confidence: 99%
“…For example, in another Latino community, store owners explained that cooking demonstrations at the stores are effective in increasing the sales of the specific food items used in the demonstrations. 14 Strategies that aim to increase awareness about the availability of healthier foods at retail food outlets, such as corner stores, may also be particularly beneficial for community residents participating in the WIC program. As of 2009, the WIC food package was revised by increasing the amount for cash value vouchers specifically for purchasing fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A questionnaire was developed by the research team using a Qualtrics platform hosted by the University of Minnesota. Frequencies for setting expectations for healthy beverage intake (10 items) and making CRF/B available in home (13 items) were assessed with previously validated scales (1 = never to 5 = always) [ 31 32 ]. Frequency of role modeling intake of CRF/B was assessed with a previously validated brief calcium intake assessment tool including 15 food/beverage items [ 33 ] using parental intake as a proxy measure for role modeling intake for children.…”
Section: Methodsmentioning
confidence: 99%